2023
DOI: 10.1038/s41467-023-37947-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of tubulogenesis revealed in the sea star hydro-vascular organ

Abstract: A fundamental goal in the organogenesis field is to understand how cells organize into tubular shapes. Toward this aim, we have established the hydro-vascular organ in the sea star Patiria miniata as a model for tubulogenesis. In this animal, bilateral tubes grow out from the tip of the developing gut, and precisely extend to specific sites in the larva. This growth involves cell migration coupled with mitosis in distinct zones. Cell proliferation requires FGF signaling, whereas the three-dimensional orientati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Three larval stages were chosen to describe neural organization through the development of P. miniata. These are referred to as early larva, bipinnaria, and brachiolaria, following previous descriptions of larval development in asteroids (Byrne & Barker, 1991;Koren & Danielssen, 1857;Mayorova et al, 2016;Muller, 1852;Perillo et al, 2023). Though these stages have been described in detail by other authors, the staging used for this study is re-described here briefly to clarify the specific developmental timepoints used in following in situ hybridization experiments.…”
Section: Larval Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Three larval stages were chosen to describe neural organization through the development of P. miniata. These are referred to as early larva, bipinnaria, and brachiolaria, following previous descriptions of larval development in asteroids (Byrne & Barker, 1991;Koren & Danielssen, 1857;Mayorova et al, 2016;Muller, 1852;Perillo et al, 2023). Though these stages have been described in detail by other authors, the staging used for this study is re-described here briefly to clarify the specific developmental timepoints used in following in situ hybridization experiments.…”
Section: Larval Developmentmentioning
confidence: 99%
“…At the early stage, the ciliary band comprised two connected ventral loops: the anteriorly located transverse preoral ciliary band (TPrO) and posteriorly located transverse postoral ciliary band (TPO) (Figure 1a,b). At this stage, larvae had a functional tripartite digestive system, a pair of dorsal muscles enabling lateral contractions, circumesophageal muscles involved in digestion, and two ciliated coeloms connecting to the ciliated hydropore (Perillo et al, 2023;Strathmann, 1971) (Figure 1b,c). At the bipinnaria stage (Figure 1d), folds forming appendages developed in the ciliary band (Figure 1d,e) and longer aboral muscles were present, projecting from the apical regions towards the esophagus (Figure 1f).…”
Section: Larval Developmentmentioning
confidence: 99%
“…They also reported that knockout of Gus suppressed its gene function of Vasa clearance from somatic cells in 5‐dpf larvae 24 . In addition, Perillo et al carried out CRISPR‐Cas9‐driven knockouts of delta , six1/2 , fgfr1 , and fz1/2/7 in P. miniata 13 . They observed each effect of knockout on the tubulogenesis of late gastrula to early bipinnaria larvae.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, echinoderms are often used to study the genetic control of developmental processes and their evolution 2,3 . Among echinoderms, starfish have been used to investigate various developmental phenomena such as whole‐body regeneration, germline formation, and early specification 4‐14 . For example, gene regulatory networks (GRNs) of early specification have been unraveled in starfish embryos and compared with other echinoderms to elucidate the evolutionary transition of GRN circuits 5,6,8‐12,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation